ANALISIS PENGARUH PENERIMAAN PAJAK HOTEL, PAJAK REKLAME DAN PAJAK PARKIR TERHADAP PENDAPATAN ASLI DAERAH (PAD) (STUDI EMPIRIS PADA KABUPATEN/KOTA DI PROVINSI JAWA TENGAH TAHUN 2009-2016) - Tuti Priyanti; Ayu Noviani Hanum; Ery Wibowo (Universitas Muhammadiyah Semarang, 2017)
This research is entitled Analysis of Hotel Tax Influence, Advertisement Tax and Parking Tax onRegional Original Income. The purpose of this study was to determine the effect of hotel tax, advertisement taxand parking tax on local revenue in Central Java Province in 2009-2016. The data used are Regional Original Revenue, Hotel Tax, Advertising Tax and Parking Tax forSurakarta City, Semarang City, Pati Regency, Klaten Regency and Banyumas Regency in 2009-2016 toexamine the effect of hotel tax, advertisement tax and parking tax on local revenue. The analysis techniqueused is Multiple Regression Analysis. The results showed that Hotel Tax has a partial effect on Regional Original Income with a significantvalue of 0.009, Advertisement Tax has no partial effect on Regional Original Income with a significant valueof 0.349 and parking tax does not have a partial effect on Regional Original Income with a significant valueof 0.456. While the hotel tax, advertisement tax and parking tax simultaneously affect local revenue.